Western Modernity interwoven with Chinese traditions:: Lives and identities of an emerging cosmopolitan society in late nineteenth century Shanghai - Lin, Hang (International Planning History Society Proceedings, 2018)
As one of the first Chinese cities opened to Western trade in mid 19th century, Shanghai soon became the preferred place of residence for foreign merchants and entrepreneurs in East Asia. Shanghai’s economy thrived and the people made this development possible came from various provinces of China, from the principal nations of Europe, the United States, Japan, and other Asian countries already colonised by the West. The relative importance of these communities varied from one period to another, but the barriers that separated them - languages, customs, and interests - all contributed to the fragmentation of the local society. This paper examines how different practices came to be grafted onto traditional systems and how Shanghai provided many opportunities for intercultural contacts between groups of people from vastly different backgrounds. I shall demonstrate that a new cosmopolitan society, largely modeled upon the Western modernity but interwoven with traditions from various parts of China, was rapidly emerging in Shanghai in the late nineteenth century, together with a distinctive “Shanghai identity” that shaped both Chinese and foreigners.